Distant toys, dissected bodies and reality TV: Luc Tuymans and painting in the age of ritual and new media. (1st January 2013) - Mieves, Christian
This article examines the work of Belgium painter Luc Tuymans (born 1958) and the manner in which his work deals, in particular, with the correlation between photography/film and painting. In order to scrutinise the impact of photography on Tuymans' work, the article makes extensive and critical reference also to Walter Benjamin's article 'The work of art in the age of its technological reproducibility'. It forms an ideal prism through which to explore Tuymans' work, which in recent years has embraced the new technology and media in paintings. This article further deals with the extent to which the undermining of dualities or binarisms (the pairing of concepts such as inside/out, particular/general or real/imaginary, material/spiritual, etc.) recognisable in European Modernism also thereby questions the binarisms object/representation, and how postmodern painters (and Tuymans in particular) react to this questioning.